2014
DOI: 10.1186/s40478-014-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP kinase-mediated NMDA receptor-dependent suppression of hippocampal hypersynchronicity in a mouse model of Alzheimer’s disease

Abstract: Hypersynchronicity of neuronal brain circuits is a feature of Alzheimer’s disease (AD). Mouse models of AD expressing mutated forms of the amyloid-β precursor protein (APP), a central protein involved in AD pathology, show cortical hypersynchronicity. We studied hippocampal circuitry in APP23 transgenic mice using telemetric electroencephalography (EEG), at the age of onset of memory deficits. APP23 mice display spontaneous hypersynchronicity in the hippocampus including epileptiform spike trains. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 70 publications
2
53
0
Order By: Relevance
“…These results are promising since there is a strong correlation between p38 activation and development of Alzheimer disease's model (Hensley et al, ; O'Donnell, Vereker, & Lynch, ; Savage, Lin, Ciallella, Flood, & Scott, ). In fact, in both the aging process and Alzheimer disease's animal model, p38 levels are found elevated in the brain (Hensley et al, ; O'Donnell et al, ; Ittner, Gladbach, Bertz, Suh, & Ittner, ). Moreover, it has been observed that p38 activation in the brain induces the formation of senile plaques, amyloid deposits, and tau phosphorylation in animal models of Alzheimer's disease (O'Donnell et al, ; Savage et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are promising since there is a strong correlation between p38 activation and development of Alzheimer disease's model (Hensley et al, ; O'Donnell, Vereker, & Lynch, ; Savage, Lin, Ciallella, Flood, & Scott, ). In fact, in both the aging process and Alzheimer disease's animal model, p38 levels are found elevated in the brain (Hensley et al, ; O'Donnell et al, ; Ittner, Gladbach, Bertz, Suh, & Ittner, ). Moreover, it has been observed that p38 activation in the brain induces the formation of senile plaques, amyloid deposits, and tau phosphorylation in animal models of Alzheimer's disease (O'Donnell et al, ; Savage et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Place cell abnormalities have been reported in several mouse models of AD (Cacucci et al, 2008;Cheng and Ji, 2013;Zhao et al, 2014;Cayzac et al, 2015;Booth et al, 2016). Moreover, disturbed theta and gamma oscillations in the hippocampus have been observed in transgenic and Ab injection models of AD (Villette et al, 2010;Rubio et al, 2012;Cheng and Ji, 2013;Ittner et al, 2014;Schneider et al, 2014;Cayzac et al, 2015;Ciupek et al, 2015;Gillespie et al, 2016;Iaccarino et al, 2016). However, to our knowledge, no previous study has assessed rhythmic coordination of place cells by slow and fast gamma oscillations in an AD mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in theta oscillation power has also been observed in other genetically modified AD mice models such as 3xTg (Mondragon-Rodriguez et al, 2018), CRND8 (Goutagny et al, 2013), and APP23 transgenic AD mice models (Ittner et al, 2014). However, in addition to the reduction of theta oscillation power, hypersynchrony and epileptic activities were also observed in transgenic AD mice models (Bezzina et al, 2015; Ittner et al, 2014; Palop and Mucke, 2010) which was absent in the AβO-injected mice in ours and other studies (Kalweit et al, 2015). Hence, long-term effects of AβO may cause differing effects on the hippocampal neural circuits, which will require further investigation.…”
Section: Discussionmentioning
confidence: 87%